2014
DOI: 10.1126/science.1251102
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy Based on Mutation-Specific CD4+ T Cells in a Patient with Epithelial Cancer

Abstract: Limited evidence exists that humans mount a mutation-specific T cell response to epithelial cancers. We used a whole-exomic-sequencing-based approach to demonstrate that tumor-infiltrating lymphocytes (TIL) from a patient with metastatic cholangiocarcinoma contained CD4+ T helper 1 (T(H)1) cells recognizing a mutation in erbb2 interacting protein (ERBB2IP) expressed by the cancer. After adoptive transfer of TIL containing about 25% mutation-specific polyfunctional T(H)1 cells, the patient achieved a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,314
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,508 publications
(1,348 citation statements)
references
References 25 publications
24
1,314
0
10
Order By: Relevance
“…Although well‐differentiated/dedifferentiated (WD/DD) liposarcomas may have a low mutation burden and are driven through overexpression of MDM2 and CDK4, DD liposarcomas can acquire additional mutations, ultimately becoming highly mutated 18. Highly mutated tumors are more genetically heterogeneous and may provide multiple immunogenic mutated protein targets for T cells, which subsequently may be inhibited at checkpoints such as PD‐1 19, 20. Indeed, recently presented provisional data have indicated that treatment with checkpoint inhibitors can result in a benefit in patients with certain sarcoma subtypes such as UPS 21…”
Section: Introductionmentioning
confidence: 99%
“…Although well‐differentiated/dedifferentiated (WD/DD) liposarcomas may have a low mutation burden and are driven through overexpression of MDM2 and CDK4, DD liposarcomas can acquire additional mutations, ultimately becoming highly mutated 18. Highly mutated tumors are more genetically heterogeneous and may provide multiple immunogenic mutated protein targets for T cells, which subsequently may be inhibited at checkpoints such as PD‐1 19, 20. Indeed, recently presented provisional data have indicated that treatment with checkpoint inhibitors can result in a benefit in patients with certain sarcoma subtypes such as UPS 21…”
Section: Introductionmentioning
confidence: 99%
“…A previous study shows that adoptive transfer of HLA-DP4-restricted NY-ESO-1-specific CD4 + T cells results in tumor regression in a metastatic melanoma patient [201]. Indeed, a recent study shows that adoptive transfer of mutation-specific CD4 + T cells results in the regression of metastatic cholangiocarcinoma (an epithelial cancer) in a cancer patient [202], suggesting that tumor-specific CD4 + T cells are capable of mediating tumor regression in epithelial cancers.…”
Section: Tcr-engineered T Cell Immunotherapymentioning
confidence: 99%
“…Meanwhile, a single T cell can be isolated and tested for its reactivity against newly identified neoantigens. Neoantigen-specific T cells can be expanded for adoptive T cell therapy, as demonstrated for ERBB2IP (E805G) and KRAS (G12D) [60,202,240], or used to identify neoantigen-specific T cell receptors (TCRs). These neoantigen-specific TCRs are cloned into expression vectors for further engineering of T cells in TCR-based immunotherapy.…”
Section: Identifying Neoantigens Recognized By Cd8 + T Cellsmentioning
confidence: 99%
See 2 more Smart Citations